Family knowledge about precipitating factors of asthmatic crisis in children - Caetano, Joselany Áfio; Lima, Maria Alzete de; Soares, Enedina; Miranda, Maira di Ciero (Rev Rene, 2010)
This study aimed to investigate how much families know about precipitating factors for asthmatic crisis in children; to identify their actions when a crisis occurs and the resources used to control it. It is a Cross-sectional and descriptive research, involving 50 relatives of children with asthma, using structured interviews. The results of the study show higher prevalence of asthma in children from 1 to 7 years old and that their relatives’ knowledge on this disease remains superficial. The most mentioned prevention measures were to avoid: dusty environments, barefoot walking, drinking cold water, exposure to smoke, contact with plush toys or animals. Frequent cough, “tight chest” and breathing difficulties were the most cited symptoms. Programs need to be created to develop health education actions with these families, addressing lifestyle, prevention of crisis exacerbation and treatment adherence.